1976
DOI: 10.1007/bf00456358
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary deafness in the Dalmatian dog

Abstract: The temporal bones from 18 deaf Dalmatian dogs were examined with the light microscope, and the cochleo-saccular degeneration process studied. End organ degeneration is already advanced by the age of 4 weeks, whilst loss of neurons in the spiral ganglion was found only in adult animals. Both processes are first evident in the central portion of the cochlea, and increase in extent with advancing age, The implications of these findings for the management of non-conductive hearing loss in man are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1
1

Year Published

1977
1977
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 30 publications
0
26
1
1
Order By: Relevance
“…Indeed, the spiral ganglion cell count was found normal in the 82 day-old puppies but spiral ganglion neuron loss was already observed in 131 day-old puppies and massive neuronal loss was observed in at least two 148 dayold puppies. In the progressive sensorineuronal degeneration previously described in dogs as well as in other species, the retrograde neuronal degeneration is usually slow and a time lag of several months to years separates CortiÕs organ degeneration and spiral ganglion neuron loss (Igarashi et al, 1972;Mair, 1976;Steel and Bock, 1983;Nadol et al, 1989;Wilkes and Palmer, 1992;Niparko and Finger, 1997;Miura et al, 2002). Our observation differed from this description in that the spiral ganglion neurons disappeared early after the CortiÕs organ degeneration in Pointer cross-puppies.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Indeed, the spiral ganglion cell count was found normal in the 82 day-old puppies but spiral ganglion neuron loss was already observed in 131 day-old puppies and massive neuronal loss was observed in at least two 148 dayold puppies. In the progressive sensorineuronal degeneration previously described in dogs as well as in other species, the retrograde neuronal degeneration is usually slow and a time lag of several months to years separates CortiÕs organ degeneration and spiral ganglion neuron loss (Igarashi et al, 1972;Mair, 1976;Steel and Bock, 1983;Nadol et al, 1989;Wilkes and Palmer, 1992;Niparko and Finger, 1997;Miura et al, 2002). Our observation differed from this description in that the spiral ganglion neurons disappeared early after the CortiÕs organ degeneration in Pointer cross-puppies.…”
Section: Discussioncontrasting
confidence: 82%
“…The degeneration of the spiral ganglion is delayed by months to years (Mair, 1976;Strain, 1996;Niparko and Finger, 1997). Cochleosaccular degeneration has been commonly described in Dalmatian in which the inherited nature of deafness has been well documented although the mode of inheritance remains controversial (Greibrockk, 1994;Famula et al, 1996Famula et al, , 2000Famula et al, , 2001Muhle et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Despite the large span within groups (4 weeks in young animal groups and 1 year in old animal groups), the variation is still quite low, which is also indicating slow degeneration of spiral ganglion neurons. Slow retrograde degeneration of spiral ganglion neurons has also been reported in other animal mutants with genetic deafness, such as the NIH strain of waltzing guinea pigs (Webster and Webster, 1981), deaf white cats (Mair, 1973) and Dalmatian dogs (Mair, 1976). The efficacy of cochlear implants in deaf patients is expected to correlate with the number of excitable spiral ganglion neurons.…”
mentioning
confidence: 93%
“…Although inherited deafness of Dalmatian dogs has been recognized since the last century [6], the mode of inheritance has not been totally determined. Several authors have reported histopathologic findings of the inner ear of deaf Dalmatians [6][7][8][9][10][11][12][13]. The histopathological patterns vary, as do those in humans with cochleosaccular dysplasia.…”
Section: Introductionmentioning
confidence: 96%
“…It is well established that genetic deafness occurs in many animals, including mice [3], cats [4], minks [5] and dogs [6][7][8][9][10][11][12][13]. In mice, deafness is combined with a locomotive disturbance of various types and grades.…”
Section: Introductionmentioning
confidence: 99%